The Impact of COVID-19 on Primary Care General Practice Consultations in a Teaching Hospital in Shanghai, China - Xu, Zhongqing; Fan, Jingchun; Ding, Jingjing; Feng, Xianzhen; Tao, Shunyu; Zhou, Jun; Qian, Lingmei; Tao, Kun; Hambly, Brett D.; Bao, Shisan (Frontiers in Medicine, 2021)
Background The COVID-19 pandemic is deeply concerning due to its massive mortality and morbidity, creating adverse perceptions amongst patients likely to impact on their overall medical care. Thus, we evaluated the impact of the COVID-19 pandemic on the pattern of primary care consultations within a Shanghai health district. Methods A retrospective observational cohort study was performed, with data analysed concerning the pattern of patient visits to general practitioners within the Tongren Hospital network (the sole provider of general practice to the population of 700,000. Data from all GP consultations for adults were collected for the first 6 months of 2020, that included a 60 day lockdown period (24 January- 24 March 2020) and compared to corresponding data from the first 6 months of 2019. We evaluated changes to the numbers and patterns of primary care consultations, including sub-group analysis based on age, sex and primary diagnosis. Results A substantial reduction in patient visits, associated with increased median age, was observed during the first wave of the pandemic in the first 6 months of 2020, compared to the same interval during 2019. Additionally, reduced reappointments and waiting times, but increased cost per visit were observed. When analysed by primary disease diagnosis, patient visits were reduced for all the major systems. The most striking visit reductions were in CVD, respiratory, endocrine and GI. However, psychological disorders were increased followed lockdown, but there was also a dramatic fall in consultations for depression. Reduced monthly patient numbers correlated with both rate of reappointment and average waiting time during the first 6 months of both 2019 and 2020, but an inverse correlation was observed between cost per visit and monthly patient numbers. Specifically during the lockdown period there was ~50% reduced patient visits. Conclusions The lockdown has had a serious impact on patients’ physical and psychological health. Our analysis provides objective health-related data that may inform the current controversy concerning the balance between the detrimental effects of the use of lockdown versus the use of a more targeted approach to eliminate viral transmission. These data may improve decision-making in medical practice, policy and education.